Crime Investigations: The Countability Profile of a Delinquent Noun - Scott Grimm (Baltic International Yearbook of Cognition, Logic and Communication, 2016)
This paper aims to broaden our understanding of countability beyond what is found with concrete nouns, providing a one-word case study of the countable and non-countable uses of the noun crime. I show that the behavior of crime runs counter to a variety of expectations inherited from the literature on countability: its countable use cannot be directly grounded in atomic acts or events, nor is its non- countable use simply equivalent to a plural individual composed of individual crimes, as one might expect on analogy with certain analyses of furniture. Additionally, while crime has a use as a bare plural, that use does not refer to a kind. A quantitative study supports these conclusions. Altogether, crime demonstrates a novel noun type with respect to its nominal semantics and countability behavior, which is also an indication of the large empirical terrain that awaits exploration for eventive and abstract nouns.
Keywords: countability; nouns; non-countable nouns; countable nouns